2016
DOI: 10.1080/14670100.2015.1102456
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the psychosocial impacts of cochlear implants on adult recipients and their partners

Abstract: Overall, CI use has been shown to have significant benefit to psychosocial well-being of CI recipients. This benefit is also conferred to their caregivers/partners; which in our society concerned about caregiver burden is quite important to recognize.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 24 publications
0
14
0
1
Order By: Relevance
“…Prior work by Wiley and Meinzen-Derr found that children with married parents were 5.7 times more likely to be referred for CI evaluation as compared to children without married parents, even after controlling for a host of factors including degree of hearing loss, insurance status, and gender. 16 Of course, improvement in psychosocial measures have been demonstrated for adult cochlear implant recipients and their spouses, 17 and cochlear implantation surgery requires extensive follow up and hearing rehabilitation, making spousal support a potentially vital component for pursuing surgery and ultimate success. 18 This finding deserves additional study for the role of marital status on the decision to pursue cochlear implantation surgery in adults.…”
Section: Discussionmentioning
confidence: 99%
“…Prior work by Wiley and Meinzen-Derr found that children with married parents were 5.7 times more likely to be referred for CI evaluation as compared to children without married parents, even after controlling for a host of factors including degree of hearing loss, insurance status, and gender. 16 Of course, improvement in psychosocial measures have been demonstrated for adult cochlear implant recipients and their spouses, 17 and cochlear implantation surgery requires extensive follow up and hearing rehabilitation, making spousal support a potentially vital component for pursuing surgery and ultimate success. 18 This finding deserves additional study for the role of marital status on the decision to pursue cochlear implantation surgery in adults.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, expectations about the success of implantation may be partly related to psychosocial health . If their hearing ability after cochlear implantation was even better than expected, then their new situation with CIs and a relatively good hearing ability might be regarded as very satisfactory . For some adults, CI serves as a way to “coming back to life.”…”
Section: Discussionmentioning
confidence: 99%
“…[28] Similarly, adult cochlear implantation not only results in enhanced auditory and speech perception abilities, but is also proven to have a positive impact on adult CI recipients' social functioning, self-esteem and educational and vocational opportunities. [29][30][31][32][33] The history of cochlear implantation internationally On 9 January 1961, Dr William F. House (otologist) and Dr John Doyle (neurosurgeon) performed the first true CI surgery by inserting a single-channel electrode inside the cochlea through the round window. [34] Following the Food and Drug Administation (FDA)'s first approval of the single-channel implant for adults in 1984, [35] remarkable and rapid improvements to CIs were made.…”
Section: Cmementioning
confidence: 99%